Analyzing The Impact of Entrepreneurial Motivation on Motives of Sustainable Environmental Adaptation: A Survey Study of The Opinions of a Sample of Employees in Smartphone Trading Companies in Al-Diwaniyah City - Rasha Neamah; Omaima Tomas; Zainab Kareem (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
The current research aims to analyse the impact of entrepreneurial motivation represented in (entrepreneurial passion, entrepreneurial self-efficacy, entrepreneurial Autonomy, entrepreneurial achievement) on the motives of sustainable environmental adaptation by (economic motives, social motives, environmental motives) for a sample of workers in smartphone trading companies in the city of Al-Diwaniyah by three companies (Dar Al-Dhal, Al-Ghad Al-Mashreq, Glitter Al-Lens). This study addresses the research problem, which has been classified as an important question: (Is it possible to analyse the impact of entrepreneurial motivation on Motives of Sustainable Environmental Adaptation among workers in smartphone trading companies in the city of Al-Diwaniyah?). In order to detect the level of research variables and analyse their results, the questionnaire tool was relied upon as a mechanism to collect the necessary data from the research sample, As a result, (130) were distributed and (121) questionnaires were retrieved from them, with (9) being damaged. This indicates that (112) are valid for analysis. To analyse and extract the results, two packages (SPSS & AMOS) were relied upon to analyse the results and test hypotheses. Based on this, the research reached a set of results, the foremost of which was the existence of a significant correlation between entrepreneurial motivation and sustainable environmental adaptation. This implies the keenness of the concerned companies to invest in the entrepreneurial motivation of improving the motives for sustainable environmental adaptation towards their workers. The research provided a set of recommendations, the most important of which is that the concerned companies should encourage work teams to develop creative solutions that reduce the economic, social, and environmental impact, such as designing phones that can be disassembled and updated.